From Afterthought to Forefront: Transforming Agricultural Resilience through CoDesigned Socio-Technical Innovations - Cosmas Kweyu Lutomia; Dessalegn Molla Ketema; Eileen Bogweh Nchanji (CGIAR Initiative on Gender Equality, 2024)
Although social innovations are recognized as important to enabling technology use, when implemented, they are often considered as an afterthought or rarely co-designed with beneficiaries. The study used data collected from 783 farmers in three counties of Kenya to assess effectiveness co-designed socio-technical innovation bundles (conservation agriculture practices and inclusive, gender-sensitive, and policy-supported innovations) in enhancing climate resilience and productivity. Results indicate significantly higher resilience capacities among users of sociotechnical innovation bundles than non-users. Significant differences in agricultural output were reported, with users demonstrating higher productivity in maize (545 kg/acre vs. 398 kg/acre) and beans (237 kg/acre vs 187 kg/acre) under climate change. The effect of bundles on productivity was higher when co-designed for both crops – maize (556 kg/acre vs 520 kg/acre) and beans (240 kg/acre vs. 231 kg/acre). However, no significant differences were reported regarding the effect of co-designed socio-technical innovation bundles on farming households’ capacity to obtain support from community/local groups in times of climate-related shocks. These findings underscore the importance of co-designing and integrating socio-technical innovations into agricultural programs.